BEARING REACTION OF OLIVE OIL MILL WASTEWATER IN VARIOUS LITHOLOGY ROCKS - Περδικάτσης, Β.; Μανούτσογλου, Ε.; Σπάρταλη, Ν.; Μωραϊτης, Δ.; Πεντάρη, Δ. (Bulletin of the Geological Society of Greece, 2004)
The olive oil production countries are currently faced with the major problem of dealing with olive oil mill wastewater. Effective treatment of these organic liquid wastes (katsigaros) has not been proposed yet. The common practice followed the last fifteen years in the island of Crete includes the creation of open wastewater evaporation ponds. The present work studies the sorption of organic agents, more specifically the phenolic compounds, in various lithology rocks. Three different samples were tested including Neogene marl-calcareous marl from Platania/Kissamou (PLA) area, schistolithic rock from Sarakina/Selinou (SAR) area and Neogene marl-siliceous (diatomite) marl successions from Basilies/Heraklion (VAS). The organic liquid wastes affect differently the PH and electrical conductivity from the studied rocks with different mineralogical composition. Rocks containing lllite show a significant adsorption of the phenolic compounds. Similar behavior is observed for the Neogene marl-siliceous (diatomite) samples, while the schistolithic rock show the lowest adsorption. The katsigaros dissolve the calcite and iron minerals and increases the CaO and Fe203 in the liquid waste.